Keberagaman produk dan pertumbuhan ekonomi: panel data atas 6 negara Asean - Sofyan, Joel Farouk; Mat Ghani, Gairuzazmi (Jurnal Ekonomi, 2018)
Recent empirical works observe a statistically positive correlation between the extent of product variety and economic growth in a broad dataset in general and the developed countries in particular. However, no research has ever been conducted so far to study this linkage exclusively in developing countries dataset. Exploiting the full dimension of ASEAN-6s data for the period of 1989-2008 at growth level, this study finds three pieces of evidence. The index of export variety positively and significantly affects per capita income, while it insignificantly influences labor productivity. Second, the index of import variety is found to insignificantly influence for both per capita income and labor productivity. The immediate conclusions drawn out from these findings are that the main characteristic of economic growth experienced by ASEAN-6s’ countries resembles that of extensively capital accumulation model and strongly outward-oriented pro-trade regime. Therefore, this study parallels with earlier studies of Funke and Ruhwedel (2001, 2005) and Saviotti and Frenken (2008), while provides additional insight for Young (1995).